Eco-friendly management of fruit fly for quality guava production - R, Chandana M; M, Menaka; Singh, Sanjay Kumar; Goswami, Amit Kumar; Sree, Mude Ramya (Indian Horticulture, 2023)
Guava is the most popular and remunerative fruit crop. It bears twice a year, the rainy season crop is normally discouraged since it bears fruits of poor quality having high fruit fly infestation (up to 86.0%). Hence, proper integrated care would yield quality fruits. Different IPM modules have been suggested which can be adopted by the guava growers, to enhance the yield of quality marketable fruits thus minimizing the use of harmful chemical insecticides. These IPM modules and other safe options need to be popularized amongst growers for producingresidue-free fruits that would fetch higher market price.